2016
DOI: 10.1007/s12152-016-9264-9
|View full text |Cite
|
Sign up to set email alerts
|

Can Medical Interventions Serve as ‘Criminal Rehabilitation’?

Abstract: ‘Moral bioenhancement’ refers to the use of pharmaceuticals and other direct brain interventions to enhance ‘moral’ traits such as ‘empathy,’ and alter any ‘morally problematic’ dispositions, such as ‘aggression.’ This is believed to result in improved moral responses. In a recent paper, Tom Douglas considers whether medical interventions of this sort could be “provided as part of the criminal justice system’s response to the commission of crime, and for the purposes of facilitating rehabilitation (Douglas in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 7 publications
0
14
0
2
Order By: Relevance
“…She claimed that two unusual punishments for criminals—making them relive their crimes from the victim’s perspective or making them sleep for half of the day—are justified under Douglas’s reasoning as long as they do not involve more suffering and coercion than Douglas’s idea of ‘minimal incarceration’, so that reasoning must be mistaken. But by Barn’s admission, even those punishments inflict minimal suffering and coercion—less than most prisoners already experience 34. No intervention I recommend for mandatory MBE is invasive (puncturing the body) or likely to harm recipients by reducing their health or capabilities at the doses I recommend.…”
Section: Lithium For Violent Offenders As Mbementioning
confidence: 97%
See 2 more Smart Citations
“…She claimed that two unusual punishments for criminals—making them relive their crimes from the victim’s perspective or making them sleep for half of the day—are justified under Douglas’s reasoning as long as they do not involve more suffering and coercion than Douglas’s idea of ‘minimal incarceration’, so that reasoning must be mistaken. But by Barn’s admission, even those punishments inflict minimal suffering and coercion—less than most prisoners already experience 34. No intervention I recommend for mandatory MBE is invasive (puncturing the body) or likely to harm recipients by reducing their health or capabilities at the doses I recommend.…”
Section: Lithium For Violent Offenders As Mbementioning
confidence: 97%
“…However, Douglas33 showed that almost any argument for protecting this right of violent offenders extends to protecting their freedom of movement and association, which imprisonment already violates. Barn34 replied that criminals’ bodily integrity is indeed analogous to those freedoms because neither should be violated on rehabilitative grounds. Yet, even if imprisonment is unjustifiable, rehabilitation including MBE may be a better alternative to prison.…”
Section: Lithium For Violent Offenders As Mbementioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of retribution, criticisms of criminal justice policies and practices usually rather relate to the means by which the goals are strived aftersuch as mass incarcerationthan to the acceptability of the goals themselves (see e.g. [51][52][53][54]). Accordingly, it would seem that even neuroenhanced criminal justice authorities would strive after goals such as those just listed above.…”
Section: Challenging the Moral Views Of The Publicmentioning
confidence: 99%
“…Two papers in this issue raise a number of objections to my argument, and I am grateful to their authors—Elizabeth Shaw and Gulzaar Barn—for subjecting it to critical scrutiny [ 2 , 3 ]. In this article, I respond to some of their objections, beginning with those offered by Shaw.…”
mentioning
confidence: 99%